Pengaruh Kegiatan Bernyanyi Terhadap Perkembangan Bahasa Anak Kelompok B Di TK Dharma Wanita Sambirejo 5 Kedungmiri, Kecamatan Mantingan, Kabupaten Ngawi Tahun Pelajaran 2015/2016 - Muhayati, Imanda Nur; , Drs. Amrul Choiri, M.Ag; , Junita Dwi Wardhani, S.E, M.Ed (2016)
The purpose of this study was to determine the influence singing activity to the development language of child at group b in kindergarten Dharma Wanita Sambirejo 5 Kedungmiri, District Mantingan, Regency Ngawi In Academic 2015/2016. This research is a kind of experiment with one group pretest-posttest Design.Subyek this study is children in group B in TK Dharma Wanita Sambirejo 5 Kedungmiri totaling 20 children. The data collection techniques in this study using observation, while the technique of data analysis using descriptive analysis and inferential analysis. Descriptive analysis is used to determine the language development of children before and after a given experiment while inferential analysis to test the hypothesis using T test in SPSS 16.0 for windows ie Paired sample t-test. Based on the analysis of the research results obtained using t-test tcount -25.342 -1.729 ≤ -ttabel ie with probability 0.000. The probability of 0,000 <α = 0.05, the null hypothesis (Ho) is rejected and Ha accepted which means there are the influence singing activity to the development language of child at group B in kindergarten Dharma Wanita Smbirejo 5 Academic 2015/2016.